Comparative Study Of Nanoporous Carbon Converted From Waste Tyre Char & Mesocarp Fiber - Ong, Guat Ling (Universiti Sains Malaysia, 2017)
Wastes with a little commercial value and have high carbonaceous value can be utilized to synthesize low cost nanoporous activated carbon (AC). AC produced from some wastes have high surface area and porosity can be used for various adsorption purposes. In this study, powdered activated carbon (PAC) and activated carbon fiber (ACF) were synthesized from waste tyre char (WTC) and mesocarp fiber (MF) at different carbonization temperatures in nitrogen gas atmosphere and followed by CO2 gas activation at 900ºС. The carbonization temperatures used were 500ºС, 600ºС and 700ºС. The physical properties of the PAC and ACF samples were studied and compared. The PAC and ACF samples produced were then used for removal of p-Cresol. The comparison showed that ACF was a good potential adsorbent for p-Cresol with a higher adsorption capacity than that of PAC. Decrease of carbonization temperatures resulted in the increase in p-Cresol adsorption predominantly due to increase in surface area. The best ACF sample was found carbonized at 500ºС having an excellent surface area of 616 m2/g and adsorption capacity of 58.2 mg/g.